Enhancing Educational Ecosystems: Implementing Peter Senge's Learning Organization Model in Islamic Boarding Schools - Husaini Zuhri, Hilmi; Huda, Miftachul (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
The inability of pesantren in the 21st-century era of knowledge and technology to maintain its classical madrasah system raises significant questions. Therefore, understanding how Madrasah Hidayatul Mubtadiin (MHM) in Lirboyo, Kediri City, as one of the Salafiyah Islamic Boarding Schools, adapts to its environment through the implementation of Peter Senge's five learning organization (LO) disciplines is crucial. This research adopts a qualitative approach, employing a case study methodology. Data were gathered through observations, interviews, and documentation. The findings indicate that the implementation of LO at MHM Lirboyo Madrasah aligns well with the five disciplines of a learning organization. These include: 1) Personal mastery among teachers is demonstrated through self-reflection, exemplary behavior, diligence, and consistency in adhering to institutional rules. 2) Mental models cultivated through tolerant behavior, respect, awareness of the importance of learning, high motivation for learning, and practicing akhlakul karimah (noble character). 3) Shared vision fostered through a commitment to obeying the Kiai (religious leaders), openness, sharing of vision, and socialization of programs. 4) Team learning is facilitated through open discussions and group dialogue. 5) System thinking is promoted through the involvement of administrators, coordinated work efforts, and mutual support. This research contrasts negative assessments of pesantren, which often characterize them as rural Islamic social structures entrenched in a conservative culture, as articulated by Clifford Geertz, Ahmad Syafi'i Ma'arif, and Fuad Amsyari.